Pagsinarayo kag pangabuhian implications of changes in the concept of land ownership among the Ati of Nagpana, Barotac Viego, Iloilo - Sabio, Rodolfo C.; Moratilla, Noel Christian (Quezon City Asian Center, University of the Philippines Diliman, 2023)
This qualitative study explored the implications on the impact of changes in indigenous land ownership concept and utilization on the ways of life (pagsinarayo) and livelihood culture (pangabuhian) of the Ati community in Nagpana, Barotac Viejo, lloilo. The study spans across the periods commencing from the pre-Spanish-era to the colonial and contemporary times. Further, it analyzed the effects of the implementation of the new land policy (IPRA, 1997) on their livelihood and living conditions. The research methods adopted a mixed approach, utilizing in-depth interviews of respondents and key informants, and Filipino indigenous research methods.

Fourteen respondents from the Ati community were selected using purposive sampling. They were the community elders born in 1935 or earlier and with an age range gap of two decades. This diverse group encompassed professionals, non-professionals, and individuals with extensive knowledge of the Ati community's history and customs. Seven key informants representing important stakeholders involved in land-related policies and initiatives were also interviewed.

The findings revealed that the changes in the legal policies affected the Ati 's fundamental understanding of land ownership, utilization and management based on their customary laws. Under the Indigenous Peoples' Rights Act (IPRA) or (RA 8371 ), the stewardship concept had been replaced with full ownership of their lands. The Ati had been participating in the projects introduced by the concerned agencies of the government thereby increasing their systems of production. As a result of this new policy, they believed that their living conditions improved. The Ati community, with the perceived security in land ownership, experienced notable improvements in its modes of production. Being sedentary, their traditional hunting and gathering practices have given way to their transformation. They had transitioned from being stewards of the lands and natural resources to embracing an identity as landowners, a change that has fostered their integration into the broader society. The implications of the land policy had clearly resulted in the change in their ways of life and living conditions. However, they had managed to retain their own cultural and traditional beliefs, practices, and language as part of their indigeneity. This development unfolds within the socio-cultural and political frameworks established by the government, providing a context for their evolving roles in the community and as part of the larger society.

Keywords: Ati of Nagpana, land ownership, legal policy changes, land use, indigenous concepts and customary practices, living conditions, indigeneity identity, Indigenous Peoples' Rights Act (IPRA), Filipino indigenous research, native values on land, socio-cultural transformation
Thesis (Doctor of Philosophy in Philippine Studies)--University of the Philippines Diliman
Keywords: Indigenous peoples -- Legal status, laws, etc. -- Philippines; Indigenous peoples -- Land tenure -- Philippines